Childhood Obesity, Epidemiology, Metabolic Consequences and Evidence-Based Preventive Strategies (Medical Forum Monthly, 2026)
Objective: To review the epidemiology, metabolic consequences, preventive measures, and evidence-basedmanagement strategies for childhood obesity.Study Design: Structured narrative reviewPlace and Duration of Study: This study was conducted through searches of PubMed/MEDLINE, Scopus, Web of Science, Cochrane Library, and Google Scholar for relevant publications from January 2016 to June 2026.Methods: Guidelines and reports from recognized organizations, including the World Health Organization andAmerican Academy of Pediatrics, were also reviewed.Results: The reviewed evidence demonstrated a substantial global rise in childhood obesity, particularly in low- and middle-income countries experiencing urbanization, dietary transition, reduced physical activity, and increased sedentary behavior. Childhood obesity was consistently associated with insulin resistance, dyslipidemia, hypertension, type 2 diabetes mellitus, metabolic dysfunction-associated steatotic liver disease, obstructive sleep apnea, and adverse psychosocial outcomes.Conclusion: Childhood obesity requires a comprehensive, non-stigmatizing, and stepped-care approach. Early prevention, structured lifestyle treatment, timely pharmacotherapy, and metabolic/bariatric surgery for eligible adolescents can reduce obesity-related complications and improve long-term health outcomes.